Where Does the First Year Students’ Level of English Language Skills Stand in CEFR A Study from Early Childhood Teacher Education Department - Nina Afria Damayanti; Woro Endah Sitoresmi; Herlini Herlini; Nur Asma; Velma Alicia (International Journal of Social Science and Humanity, 2024)
This study aims to reveal the proficiency level of English language skills among first-year students in the Early Childhood Education department at Universitas Negeri Medan. The skills assessed in this study include grammar, reading comprehension, writing proficiency, listening comprehension, and oral communication. This study employed a quantitative research methodology, focusing on first-year students who are enrolled in English language courses. Throughout the research process, the researchers refrained from administering any interventions to the samples. The acquired data from the samples undergoes analysis using descriptive statistics. The analysis indicates that 70% of the students demonstrated proficiency at the A2 level, which corresponds to basic English usage according to the Common European Framework of Reference (CEFR). This level corresponds to the English language proficiency of elementary kids. Based on this study, it is necessary to enhance the English language curriculum utilized in the Department of Early Childhood Education to align with the students' English language competence level.